Integrated Marketing Communication Strategy in Computer Hardware Industry: A Case Study on PT. IZZM - Chandrawinata.Ng*, Calvin; Dhewanto, Wawan (Universitas Syiah Kuala, 2024)
This study addresses PT. IZZM's struggle to sell power supply units (PSUs) despite success in motherboard sales. Recognizing the importance of PSUs in computers, the author proposes an Integrated Marketing Communication (IMC) strategy to enhance brand awareness and customer purchase intention within the competitive power supply market in Indonesia. Recognizing the growing significance of effective communication strategies, this study combines both quantitative and qualitative research methodologies to formulate a robust strategy tailored to the unique characteristics of the Indonesian market. The results of this quantitative research will provide valuable insights into the market dynamics and facilitate the development of targeted communication strategies. Complementing the quantitative research, the qualitative aspect employs in-depth interviews to gain a deeper understanding of consumer perceptions, preferences, and emotional connections to power supply brands. Based on the findings from both quantitative and qualitative research, the proposed IMC strategy integrates various communication channels such as digital marketing, social media engagement, influencer collaborations, public relations, and traditional advertising. Special attention is given to cultural nuances and localized communication strategies to ensure resonance with the Indonesian target audience. This project aims to provide PT. IZZM with a strategic roadmap to enhance its market presence in Indonesia, fostering increased brand awareness and positively influencing customer purchase intention in the power supply segment. The combination of quantitative and qualitative research methodologies ensures a well-rounded and data-driven approach to inform the development and implementation of an effective Integrated Marketing Communication strategy.